2016
DOI: 10.1097/jom.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons–Associated MicroRNAs and Heart Rate Variability in Coke Oven Workers

Abstract: Plasma miRNAs might act as potential biomarkers for the adverse effect of PAH exposure on the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We propose miR-142-5p, miR-655-5p, and miR-196a-1-5p as miRNAs with a high and stable expression in plasma exosome, stool, and urine respectively, while piR-43137, chr6.tRNA59-IleAAT, and piR-33543 as the candidate references among other sncRNAs in plasma exosomes, stool, and urine respectively. miR-142-5p has been found dysregulated in plasma but not in exosomes [ 47 49 ] although it has been demonstrated that in rats the activation of the acute stress response modifies its profile in plasma exosomes [ 50 ]. miR-655-5p and miR-196a-1-5p have never been studied in stool and urine, except for miR-196a reported to be altered in focal segmental glomerulosclerosis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose miR-142-5p, miR-655-5p, and miR-196a-1-5p as miRNAs with a high and stable expression in plasma exosome, stool, and urine respectively, while piR-43137, chr6.tRNA59-IleAAT, and piR-33543 as the candidate references among other sncRNAs in plasma exosomes, stool, and urine respectively. miR-142-5p has been found dysregulated in plasma but not in exosomes [ 47 49 ] although it has been demonstrated that in rats the activation of the acute stress response modifies its profile in plasma exosomes [ 50 ]. miR-655-5p and miR-196a-1-5p have never been studied in stool and urine, except for miR-196a reported to be altered in focal segmental glomerulosclerosis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-145is highly expressed in vascular smooth muscle cells (VSMC) and it controls the differentiation of VSMC into a functional phenotype, thus protecting against lesion formation (Rangrez et al, 2011;Wei et al, 2013). To date, few investigations have evaluated miRNAs expression profiles in populations exposed to PAHs (Deng et al, 2014a(Deng et al, , 2014bHuang et al, 2016;Woeller et al, 2016). The data found in this research have demonstrated a significant increase in the plasmatic expression levels of miR-126, and miR-155 in women highly exposed to PAHs (T2 and T3) compared to miRNAs expression levels in women with low exposure to PAHs (T1) (Figs.…”
Section: Plasma Mirnas Expression Levelsmentioning
confidence: 99%
“…The studies included in this review showed evidence that exposure to PAH was associated with the presence of cardiovascular diseases and aggravations, such as increased blood pressure levels (22) , heart rate variation (14,(24)(25)(26) and ischemic heart disease (17,20,27) ; and respiratory diseases such as reduced lung function (23) , chronic obstructive pulmonary disease (COPD) (18)(19)28) , asthma (19) , and symptoms such as wheezing (16) , cough (16,18) , lung wheezing (19), tight chest (19) , shortness of breath on exertion (19) and sore throat (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons -associated microRNAs and heart rate variability in coke oven workers (26) .…”
Section: China Web Of Sciencementioning
confidence: 99%